Dendritic Cell-Restricted Progenitors Contribute to Obesity-Associated Airway Inflammation via Adam17-p38 MAPK-Dependent Pathway - Anil Kumar Jaiswal; Anil Kumar Jaiswal; Sangeet Makhija; Sangeet Makhija; Natalie Stahr; Natalie Stahr; Maninder Sandey; Amol Suryawanshi; Ankit Saxena; Pradeep K. Dagur; J. Philip McCoy; Stewart J. Levine; et al. (Frontiers in Immunology, 2020)
Proliferation of dendritic cell (DC)—restricted progenitor cells in bone marrow compartment is tightly regulated at steady state and responds to multiple tissue-specific triggers during disturbed homeostasis such as obesity. DCs in the lung stem from a rapidly dividing DC-restricted progenitor cells and are effective at generating adaptive immune responses in allergic airway inflammation. Precisely, how DC-restricted progenitor expansion and differentiation are influenced by airway inflammation to maintain constant supply of myeloid DCs is poorly understood. Here we show that a high fat diet (HFD) induces oxidative stress and accelerates the expansion of DC- restricted progenitor cells in bone marrow and correlates with persistent induction of p38 mitogen activated protein kinase (MAPK), which is blocked with a selective p38α/β MAPK inhibitor. Mice fed a HFD and sensitized to inhaled allergen house dust mite (HDM) led to alterations of DC- restricted progenitor cells that were characterized by increased expansion and seeding of lung DCs in airway inflammation. Mechanistically, we establish that the expansion induced by HFD dysregulates the expression of a disintegrin and metallopeptidase domain 17 (Adam17) and is required for p38 MAPK activation in DC-restricted progenitors. These results demonstrates that obesity produces persistent changes in DC precursors and that elevation of Adam17 expression is tightly coupled to p38 MAPK and is a key driver of proliferation. Altogether, these data provide phenotypic and mechanistic insight into dendritic cell supply chain in obesity-associated airway inflammation.